Analisis Penerimaan Sistem Administrasi Pajak Daring Berdasarkan Technology Acceptance Model - Antoro, Aji Fajar Suryo; Thaha, Abdurrahman Rahim; Muhtarom, Muhtarom; Sunarya, Amud; Nurhayati, Syafiqoh (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
This study examines the tax revenue and administration system of the brave in Greater Tangerang in the context of low technology adoption despite the initiation of e-government and smart city programs. The study aims to analyze the factors that influence the revenue system using the Technology Acceptance Model (TAM) framework. The method used is a quantitative approach with an explanatory research type, using Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze the relationship between variables. Data were collected from 357 taxpayer respondents through a brave questionnaire. The results of the study indicate that perceived ease of use and perceived benefits have a significant effect on attitudes and actual use of the brave tax administration system. System complexity was found to have a negative impact on ease of use, while system compatibility increased the benefits perceived by users. These findings are in line with the TAM framework, which emphasizes the importance of user perception in determining technology acceptance. To increase acceptance of the brave tax system, the government needs to prioritize complexity and improve system compatibility through user education and technical support. The results of the study provide theoretical contributions by strengthening the TAM framework in the context of public digital services, as well as providing practical recommendations for optimizing the implementation of the brave tax administration system.